A Case Study of Teacher Turnover and Retention in an Urban Elementary School - Barry Kamrath; Kim Bradford (Educational Considerations, 2020)
This mixed methods study examined the phenomenon of teacher turnover in one high poverty urban elementary school to determine common characteristics of teachers who remained long-term (> 5 years), as well as factors that contributed to teachers’ decisions to leave before reaching their sixth year. The study included structured interviews with long-term teachers and surveys of short-term teachers. Qualitative data were analyzed through constant-comparative analysis to determine emergent themes; whereas, quantitative data provided triangulation of interview data as well as the formalizing of comparisons. Long-term teachers had built deep connections to the school, its students, and the community, despite the lack of a trusting relationship with their principal. Teachers who left the school felt they lacked recognition for their efforts, and they contended with a lack of administrative support. The findings from this research suggest the most important factors contributing to teacher turnover in the high poverty urban school are primarily within control of the building administrator. Implications for urban schools and their administrators are included.
Keywords: teacher turnover; teacher retention; urban education